The Impact of Asset-Liability Management on Profitability: Evidence from Commercial Banks in Zimbabwe (Acta Universitatis Danubius. Œconomica, 2025)
This study employs the Statistical Cost Accounting (SCA) econometric framework to evaluate the impact of asset-liability management (ALM) on the profitability of Zimbabwean commercial banks. It explores how efficient ALM strategies can optimize asset allocation, mitigate bank failures, and enhance performance in volatile economic environments. Building on prior research and practical experience in bank treasury management, the paper extends the SCA model to the unique context of evolving regulatory conditions and macroeconomic volatility, addressing gaps in understanding the interplay between ALM strategies, strategic leadership, and profitability. A panel dataset of 15 Zimbabwean banks spanning 2010-2023 was analyzed using R. Quantitative methods included variance inflation factor (VIF) tests, heteroskedasticity tests, Lagrange Multiplier (LM) tests, and pooled Ordinary Least Squares (OLS) regression with robust standard errors to examine the relationships among ALM variables, macroeconomic factors (GDP growth), and return on assets (ROA) as a measure of profitability. The findings confirm ALM’s significant influence on profitability, with an adjusted R-squared of 46.51% and model significance (F-statistic, p = 0.0084). Asset management variables positively impact ROA (supporting Hypothesis 1), while liability management variables negatively affect profitability due to funding cost implications (supporting Hypothesis 2). The combined composition of assets and liabilities validates Hypothesis 3, and overall model significance supports Hypothesis 4, confirming a statistically significant relationship between ALM and profitability of Zimbabwean commercial banks. The study provides actionable insights for bank treasurers, policymakers, and regulators, emphasizing the importance of optimizing ALM practices to sustain performance and enhance balance sheet resilience. Asset-Liability Management Committees (ALCOs) can leverage these findings to identify high-return assets, refine allocation strategies, and optimize funding costs. By applying the SCA econometric model to Zimbabwe, this research addresses a critical gap in banking literature, offering a comprehensive analysis of ALM’s role in profitability. It contributes to the broader discourse on banks’ financial performance and resilience under economic uncertainty, advancing the application of the SCA framework in frontier markets.